Obtained Gratifications of Syrian Youth's Usage of Facebook as a Source of Information (Damascus University Journal of arts and humanities sciences, 2025)
The study aimed to understand the gratifications achieved by Syrian youth in using Facebook as a source of information, applied to a sample of youth aged between 18 and 35 years. It was found that their use of Facebook as a source of information is high for seeking information at a low cost. It became evident that this usage resulted in a high satisfaction level for them due to easy access to information.There was no significant relationship between the average use of Facebook as a source of information and the achieved gratifications among the study sample. Additionally, there were no significant differences among the study sample in the rate of using Facebook as a source of information and the obtained gratifications based on the gender variable. However, there weresignificant differences among the study sample in the rate of usage based on age and education level in favor of the age group of 18 to 24 years and university education level. It was also found that there were no significant differences among the study sample in the rate of gratifications obtained from using Facebook as a source of information based on age and education variables.
Keywords: gratifications; Syrian youth; Facebook; Information